The Urgence of Environmental Law Enforcement - Hadi Supriyanto (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
People are a component of the environment. Where human involvement with the environment has an effect on other forms of life. The environment evolves in tandem with societal transformations. Human survival is extremely dependent on the environment. In the social perspective, the environment (ecosystem) is a unit that cannot be separated. The influence of environmental pollution on human growth and survival is unfavorable. If the environment (ecology) is healthy, it will have a favorable effect on the development of human life's carrying capacity. On the other side, driven by limitless human wants, there is frequently excessive and unregulated exploitation of the environment, resulting in environmental harm and contamination. To counteract the negative effects of excessive environmental exploitation, it is essential to have a social engineering tool, namely the law, in order to establish an orderly society (law as a tool of social engineering). This study employs a normative legal approach as its methodology. This study will examine normatively applicable legal structures pertaining to the environment in Indonesia, with an emphasis on the necessity of law enforcement (law as a tool of social engineering). This study employs a normative legal approach as its methodology. This study will examine Indonesian environmental legal structures from a normative perspective, focusing on the urgency of law enforcement. Specifically, the law to establish an orderly society (law as a tool of social engineering). This study employs a normative legal approach as its methodology. This study will examine Indonesian environmental legal structures from a normative perspective, focusing on the urgency of law enforcement.